A consultation journey: developing a Kaupapa Māori research methodology to explore Māori whānau experiences of harm and loss around birth. (March 2018) - Stevenson, Kendall
Kaupapa Māori (by Māori, for Māori, with Māori) researchers have provided a space to undertake research that is culturally responsive, ensures the voices of Māori (Indigenous peoples of Aotearoa New Zealand) are heard, and challenges structural barriers to Māori health and wellbeing. This article describes my journey to develop a Kaupapa Māori methodology appropriate for exploring whānau (families) experiences following the harm or loss of their infant around birth. Guidance from key informants was sought and a Kaupapa Māori methodology was then developed based on their wisdom, expertise, and experience. The five components of this methodology are designed to keep all involved in this research safe: whānau (family), wāhi haumaru (providing a safe space), whakaaro (engaging in Māori philosophies), kaitiaki (being empathetic), and hononga (building and maintaining relationships). Researchers undertaking Kaupapa Māori research are invited to use this methodology, or follow a similar process to develop their own expert-informed methodology.